2021
DOI: 10.3847/1538-3881/abd409
|View full text |Cite
|
Sign up to set email alerts
|

The TESS-Keck Survey. II. An Ultra-short-period Rocky Planet and Its Siblings Transiting the Galactic Thick-disk Star TOI-561

Abstract: We report the discovery of TOI-561, a multiplanet system in the galactic thick disk that contains a rocky, ultrashort-period planet. This bright (V = 10.2) star hosts three small transiting planets identified in photometry from the NASA TESS mission: TOI-561 b (TOI-561.02,

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 121 publications
(119 reference statements)
1
39
0
Order By: Relevance
“…Examples of such recent discoveries from TESS include the TOI-561 system (Lacedelli et al 2021;Weiss et al 2020), TOI-130 system (Sozzetti et al 2021), and TOI-178 system (Leleu et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Examples of such recent discoveries from TESS include the TOI-561 system (Lacedelli et al 2021;Weiss et al 2020), TOI-130 system (Sozzetti et al 2021), and TOI-178 system (Leleu et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…TKS is a consortium performing precise RV (PRV) followup of TESS planet candidates (Dalba et al 2020;Dai et al 2020;Rubenzahl et al 2021;Weiss et al 2021). One of our group's primary science goals is to measure a diverse set of planet masses at high enough precision to be suitable for atmospheric characterization (Batalha et al 2019), particularly with the James Webb Space Telescope (JWST), which is what led us to observe HD 63935.…”
Section: Introductionmentioning
confidence: 99%
“…Because of their relatively small transit signals, such planets represent more challenging targets than similar-sized targets around M or K dwarfs. However, the brightness of the host stars can compensate for this, and a number of compelling targets for atmospheric characterization with JWST around G star hosts have already emerged from TESS (e.g., Gandolfi et al 2018;Mann et al 2020;Weiss et al 2021, Lubin et al 2021Turtelboom et al 2021, in preparation).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, Winn et al (2018) found that the radius distribution of USP planets shows a decline at a physical radius of 2 R ⊕ , indicating that USP planets tend to be small (despite discovery biases against smaller planets). Although only a limited number of USP planets have measurements of both their mass and radius, and their densities are largely consistent with rocky compositions (e.g., Grunblatt et al 2015;Weiss et al 2016;Christiansen et al 2017;Sinukoff et al 2017;Vanderburg et al 2017;Weiss et al 2021), and they often reside in multiplanet systems (Winn et al 2018;Adams et al 2020).…”
Section: Introductionmentioning
confidence: 99%